Modern Times of Living (Loving) and Working: What Has Happened to Them? - Sartori, Riccardo; Mancini, Alessandro; Ceschi, Simone (Italian Sociological Review, 2025)
The article is intended to be a reflection on modern times of living and working in the age of the smartphone and new technologies in general. Is there still, today, a clear distinction between living time and working time? Or has the smartphone, which we take as the most common and widely used representative of new technologies, made the boundaries between what were once clearly distinct living and working times increasingly blurred and con-fused? Smartphones contain all kinds of apps, from those useful or even necessary for life and work, to those for playing games, having fun and meeting people; and it is with us morning, afternoon, evening and night; weekdays and holidays; when we are well and when we are ill; when we are alone and when we are with friends. Losing it (or not being connected) is unthinkable for us and generates what is called nomophobia (NO MObile PHone PhoBIA). Another well-known fear related to new technologies in general and the smartphone in particular goes by the name of FOMO, short for “Fear Of Missing Out”, which is a worried feeling that you may miss events (both offline and, more importantly, online) that other people seem to take part in and thus run the risk of being excluded, forgotten, left out and substituted. Can all this be without consequences of various kinds? In this article, we focus on the consequences this has on our modern times of living (loving) and working.